Sheikh Saadi Rahman Baba and Sultan Bahoo's Philosophy of fulfillment - Tahir Bostan, Muhammad; Ahmad, Mazhar; Ali, Sabir (sourcecoder, 2022)
This article traces the original source of Rahman Baba' Sheikh Saadi and Sultan Bahoo's philosophy of patience. They left undeletable marks of their services in the field of philosophy, culture, religion, literature and creativity in every shape of knowledge. These three philosophers took the world to storm through their anecdotes, quotations and useful philosophical narrations. They ranked among representative poets of their times. They were great anthropologists. All their poems are based upon human friendship and sound values.